Analisis Implementasi Kurikulum Merdeka Terhadap Minat Belajar Matematika Peserta Didik TKJ SMK Swasta Teladan Pematangsiantar - Putri, Risma Aprilia; Nainggolan, Tiara; Malau, Vera Wati; Ompusunggu, Trinita Oktheresia; Simatupang, Noni Winda; Adsari, Juwita Dwi (Polinomial : Jurnal Pendidikan Matematika, 2025)
Improving the quality of education in Indonesia continues to be pursued through various curriculum innovations, one of which is the Merdeka Curriculum, emphasizing project-based, flexible, and student centered learning. This study aims to analyze the influence of Merdeka Curriculum implementation on students’ interest in learning mathematics in the Computer and Network Engineering (TKJ) program at SMK Swasta Teladan Pematangsiantar. Learning interest is a critical variable as it contributes significantly to learning effectiveness and academic outcomes, especially in mathematics a subject often perceived as challenging. A quantitative approach was applied using a survey method with a Likert-scale questionnaire distributed to 65 respondents who had experienced the Merdeka Curriculum for at least one semester. Instrument validity and reliability were tested using SmartPLS, with results showing all constructs met convergent validity (AVE > 0.5) and reliability standards (Composite Reliability > 0.9). The coefficient of determination (R²) reached 0.6405, indicating that the Merdeka Curriculum explains 64.05% of the variance in students’ interest in learning mathematics. Hypothesis testing through bootstrapping revealed a path coefficient of 0.8003, a t-statistic of 19.2392, and a p-value of 0.000, confirming a significant and positive influence. This study concludes that the Merdeka Curriculum effectively enhances students’ interest in learning mathematics, although its success depends on the readiness of teachers, educational facilities, and supportive learning environments.